2022
DOI: 10.3389/fcosc.2022.803381
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Forensics Reveal High Rates of Non-lethal Snaring and Shotgun Injuries in Zambia's Large Carnivores

Abstract: The impact of snaring and human-wildlife conflict (HWC) on large carnivore populations is of growing concern, and yet few empirical data are available. Mortality is the metric most often used, but non-lethal injuries that impact fitness are also important threats. However, because non-lethal injuries to wild carnivores are difficult to detect, they have received little study. Using straightforward forensic examination of the skulls of trophy-hunted lions and leopards from Luangwa Valley (LV) and Greater Kafue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This suggests that the direct effect of snaring on population growth rate may outweigh the reduction in reproductive success which we identified in the current study. As the cause of death in adults is often difficult to identify, indirect methods based on analyzing patterns of disappearances of individuals, for example during specific seasons associated with specific spatio-temporal risks, or forensic examinations based on snare damage to teeth (White & Van Valkenburgh, 2022), may prove useful for estimating the direct population-level effects of snaring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the direct effect of snaring on population growth rate may outweigh the reduction in reproductive success which we identified in the current study. As the cause of death in adults is often difficult to identify, indirect methods based on analyzing patterns of disappearances of individuals, for example during specific seasons associated with specific spatio-temporal risks, or forensic examinations based on snare damage to teeth (White & Van Valkenburgh, 2022), may prove useful for estimating the direct population-level effects of snaring.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their unselective nature, snares also capture non-target species, including predators attracted to carcasses in snare lines , which results in substantial bycatch (Hofer, East & Campbell, 1993;Becker et al, 2013). For instance, a recent study revealed a high proportion of non-lethal snare injuries in several carnivore species in Zambia, with evidence of snare entanglement greatly surpassing previous estimates for these regions (White & Van Valkenburgh, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There have been extensive studies of some forms of ‘human-induced’ damage to animals; for example, non-accidental injury caused to dogs and cats [ 9 , 10 ], the effects of traps and snares [ 11 , 12 ], poisoning [ 13 , 14 ], and shooting on wildlife [ 12 , 15 ]. Death, injury, health concerns, pain, or distress may result from most of the examples cited above but the implications may differ depending on the species and the circumstances surrounding the attack [ 2 , 16 ].…”
Section: Animals In Forensic Sciencesmentioning
confidence: 99%
“…The annual elephant mortalities due to illegal hunting in the Luangwa Valley have remained highest in the last two decades among wildlife landscapes in the country [31]. Furthermore, other studies in the Luangwa Valley have reported that high levels of illegal hunting by snaring had increased mortality rates and disturbed population structures of wild animals [28][29][30]36]. The pervasive and persistent illegal hunting by snaring is probably indicative of prevalent local community involvement in poaching, inadequate local community support for conservation and ineffective available measures for addressing poaching by snaring [28,37].…”
Section: Introductionmentioning
confidence: 99%